Hubungan Indeks Osilasi Selatan dan Indeks Curah Hujan terhadap Kejadian Kekeringan di Kabupaten Indramayu, Jawa Barat, Indonesia - BOEDI TJAHJONO; BABA BARUS; NINA WIDIANA DAROJATI (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2017)
Indramayu district experiences frequent droughts that leads to many paddy fields harvest failure. Since the district is one of the national granary, this disaster needs to be addressed urgently. This study aimed to assess the level of dryness in Indramayu using Standard Precipitation Index (SPI) and its relation with the Southern Oscillation Index (SOI). The study used monthly rainfall data from 1996 to 2013 observed by 19 stations and the score of SOI that came from the Bureau of Meteorology of Australia. The method used quantitative approach using SPI and software SPI_sl_6.exe. Drought indices was measured in four different time scale which are 1, 3, and 6 month(s) (for the short term period) and the 12 months time scale (for the long term period). SPI’s assessment was classified in accordance with the classification of WMO (World Meteorological Organization) which consist of seven classes, ranging from wet extreme to dry extreme class. The results showed that the occurence of "very dry" to "dry extreme“ drought was occured mainly from February 1997 to January 1998 at most stations, while for some stations, it lasted until March 1998. The drought period was lasted from nine to ten months. In 2002 to 2003, the droughts that classified as "very dry" on a 3 and 6 months time scale lasted about five months, while the 12 months time scale was lasted about nine months. SPI value that obtained from different time scales has a strong relation with the value of SOI. The negative value of SOI tends to be followed by the negative value of SPI, and vice versa. SOI that has negative value below -7 and occured in a long period (more than three months) indicates a prolonged El Nino which occurred in 1997 and 2002/2003 when the research area was struck by "being dry" to "dry extreme" drought state.